Elevated frequency of IL-37- and IL-18Rα-positive T cells in the peripheral blood of rheumatoid arthritis patients. (October 2018) - Wang, Liuqing; Wang, Yueying; Xia, Liping; Shen, Hui; Lu, Jing
Highlights: IL-37 and IL-18Rα positive T cells were significantly elevated in RA patients. IL-37 and its receptors may play an immunoregulatory role in the CD4 + T activation. IL-37 plays an important role in the regulation of inflammation in RA. IL-37 may be a therapeutic target for rheumatoid arthritis. Abstract: Objective: To detect the expression of IL-37 and its receptors IL-18Rα and IL-1R8 in CD4 + T cells and total lymphocytes in rheumatoid arthritis (RA) patients and the relationship between autoantibodies and disease activity. To investigate the mechanism of IL-37 and its receptors involved in the pathogenesis of RA. To evaluate the effects of different concentrations of rhIL-37 on peripheral blood mononuclear cells (PBMCs) in RA patients with TNF-α, and IL-6. Methods: The expression of IL-37 and its receptor IL-18Rα and IL-1R8 in peripheral blood CD4 + T cells and total lymphocytes in RA patients and healthy controls were measured by flow cytometry. The levels of TNF-α and IL-6 in the supernatant were measured by ELISA after rhIL-37 stimulation with PBMCs. Results: The expression of IL-37 and IL-18Rα in the total lymphocytes, especially in CD4 + T cells in RA patients, was significantly higher than in the healthy control group. There was a positive correlation between the frequency of IL-37- or IL-18Rα-positive CD4 + T cells and ESR, CRP, and DAS28 values. Additionally, rhIL-37 significantly down-regulated TNF-α and IL-6 production in RA patients' PBMCs. Conclusions: IL-37 plays an important role in the regulation of inflammation in RA. IL-37 and its receptors may play an immunoregulatory role in the activation of lymphocytes, especially CD4 + T cells, in RA patients. IL-37 may represent a therapeutic target for rheumatoid arthritis.